Memórias das águas: sociedades e águas no Jequitinhonha e Norte de Minas Gerais nos séculos XIX e XX - Rodolfo Ribeiro de Souza (2023)
Societies and waters are related according to social, economic, cultural, territorial and temporal contexts. Adopting the dialectical method and applying bibliographic and documentary research procedures, this work analyzes the relationships between societies and waters in the Jequitinhonha and Northern regions of Minas Gerais, in the 19th and 20th centuries, based on the records of memoirists, travelers and chroniclers. The dissertation approaches the use of the waters, which has always been orientated by a quality standard. Those standards have been diversified as the time went by, although it has never lost the relation with the conservation of human health. Since the idea of the relation between societies and nature, the authors could formulate their concept. 145 literary works referred to the studied field were read. 109 of them were useful to the dissertation, and 76 were written by memorialists, 18 by travelers, 12 were written by chroniclers and 3 by historians. This study identified knowledge systems which orientated the use of the natural resources. There are many and varied waters cultures narratives in the regions of Jequitinhonha and North of Minas Gerais. Through them, it can be seen the different ways of organization in each community with distincts cultures, that changed over time to conform the “neutral” and distants relations inserted by the intercession and actions on the interaction between society and waters.